Magnesium ferrite nanostructures for detection of ethanol vapours - A first-principles study - Veerappan Nagarajan (Processing and Application of Ceramics, 2017)
The adsorption behaviour and electronic properties of ethanol vapour on MgFe2O4 ceramic nanostructures are studied using density functional theory technique. The structural stability of MgFe2O4 nanostructure is determined with the help of formation energy. The adsorption behaviour of ethanol molecules on MgFe2O4 base material is analysed in terms of average energy gap variation, Mulliken charge transfer, band gap and adsorption energy. The most prominent adsorption sites of ethanol vapours on MgFe2O4 nanostructure are investigated at atomistic level. The density of states spectrum reveals the clear picture about the electronic properties of MgFe2O4 nanostructure. The density of states and electronic band gap confirmed the adsorption of ethanol vapours on MgFe2O4 nanostructure. The changes in the energy band gap and density of states are observed upon adsorption of ethanol vapour molecules on MgFe2O4 nanostructure. The density of states spectrum also confirms the changes in peak maxima due to the transfer of electrons between MgFe2O4 nanostructure and ethanol vapours. The adsorption of oxygen atom from ethanol vapour on iron in MgFe2O4 is found to be more prominent rather than other adsorption sites. The findings show that MgFe2O4 nanostructure can be utilized to sense the presence of ethanol vapour in the atmosphere.